PENGARUH PROFITABILITAS, RISIKO KREDIT, LIKUIDITAS, DAN EFISIENSI OPERASIONAL TERHADAP KECUKUPAN MODAL PADA BPR KABUPATEN KLUNGKUNG - Agustini, Ni Putu Ayu Ria; Artini, Luh Gde Sri (E-Jurnal Manajemen; Vol 7 No 10 (2018), 2018)
ABSTRACT This study aims to determine the effect of profitability, credit risk, liquidity and operational efficiency towards the  capital adequacy ratio in Bank Perkreditan Rakyat which located in Klungkung regency in 2013-2017. In this study the method used is multiple linear regression analysis techniques. This study used a saturated sample with a total sample of 5 BPR located in Klungkung Regency. Based on the results of the analysis that has been done, obtained the results of Profitability represented by ROA, credit risk represented by NPL, liquidity represented by LDR, and operational efficiency represented by BOPO get significant positive results on capital adequacy. 76.4 percent of the capital adequacy is affected by profitability, credit risk, liquidity and operational efficiency while the remaining 23.6 percent is influenced by other factors not included in the research model. Keyword : ROA, NPL, LDR, BOPO, capital adequacy